Repeated truncation of a modular antimicrobial peptide gene for neural context. - Hanson, M.A.; Lemaitre, B. (PLoS Genetics, 2022)
Antimicrobial peptides (AMPs) are host-encoded antibiotics that combat invading pathogens. These genes commonly encode multiple products as post-translationally cleaved polypeptides. Recent studies have highlighted roles for AMPs in neurological contexts suggesting functions for these defence molecules beyond infection. During our immune study characterizing the antimicrobial peptide gene Baramicin, we recovered multiple Baramicin paralogs in Drosophila melanogaster and other species, united by their N-terminal IM24 domain. Not all paralogs were immune-induced. Here, through careful dissection of the Baramicin family's evolutionary history, we find that paralogs lacking immune induction result from repeated events of duplication and subsequent truncation of the coding sequence from an immune-inducible ancestor. These truncations leave only the IM24 domain as the prominent gene product. Surprisingly, using mutation and targeted gene silencing we demonstrate that two such genes are adapted for function in neural contexts in D. melanogaster. We also show enrichment in the head for independent Baramicin genes in other species. The Baramicin evolutionary history reveals that the IM24 Baramicin domain is not strictly useful in an immune context. We thus provide a case study for how an AMP-encoding gene might play dual roles in both immune and non-immune processes via its multiple peptide products. As many AMP genes encode polypeptides, a full understanding of how immune effectors interact with the nervous system will require consideration of all their peptide products.